'The view from above' at Europe's maritime borders: Racial securitization from visuality to postvisuality. (October 2020) - Madörin, Anouk
At a time when the European Union is intensifying its electronic frontier through unmanned aerial vehicles or drones, and remotely piloted aircraft and satellite remote sensing devices, it is crucial to ask what this 'view from above' in effect enables. Although creating enhanced visibility in the Mediterranean basin of migrants' crossings, the technological solutions provided by the European Union do not prioritize search and rescue. In analyzing European Union policy documents regarding visibility-making at Europe's maritime borders, as well as the rationale presented by the industry delivering the technological backbone, this article shows how the 'view from above' is not only constructed through data but feeds back into data-generating 'vision machines'. The working together of the scopic/visual/ocular and the digital/algorithmic/metrical is coined 'postvisuality' – a term highlighting the entanglement of image and code and the subsuming of the visual under the digital, or digitality. Postvisuality is framed by Europe's long history of racial securitization, which in this case facilitates migrants' data doubles becoming a key locus for financialization and the generation of a surplus for the security and defense industries.